2022
DOI: 10.1038/s41598-022-18249-x
|View full text |Cite
|
Sign up to set email alerts
|

Field validation of deep learning based Point-of-Care device for early detection of oral malignant and potentially malignant disorders

Abstract: Early detection of oral cancer in low-resource settings necessitates a Point-of-Care screening tool that empowers Frontline-Health-Workers (FHW). This study was conducted to validate the accuracy of Convolutional-Neural-Network (CNN) enabled m(mobile)-Health device deployed with FHWs for delineation of suspicious oral lesions (malignant/potentially-malignant disorders). The effectiveness of the device was tested in tertiary-care hospitals and low-resource settings in India. The subjects were screened independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…A multicentric prospective study reported high accuracy for telediagnosis employing an automated mHealth-enabled, dual-image device as a point-of-care triaging tool in comparison with onsite specialists (sensitivity:95%; specificity:84%), which will empower CHWs for defining OPMD. 59 A previous study has reported enhanced compliance with workplace screening by mobile health. 61 Multi-centric study from Tamil Nadu reported that mobile technology was user-friendly, inspires CHW confidence, and decreases paper-based system time, resources, and maintenance.…”
Section: Challenges In the Health Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…A multicentric prospective study reported high accuracy for telediagnosis employing an automated mHealth-enabled, dual-image device as a point-of-care triaging tool in comparison with onsite specialists (sensitivity:95%; specificity:84%), which will empower CHWs for defining OPMD. 59 A previous study has reported enhanced compliance with workplace screening by mobile health. 61 Multi-centric study from Tamil Nadu reported that mobile technology was user-friendly, inspires CHW confidence, and decreases paper-based system time, resources, and maintenance.…”
Section: Challenges In the Health Systemmentioning
confidence: 97%
“…Recent indigenous low-cost innovations such as point-of-care diagnosis layered with artificial intelligence and machine learning are emerging adjunct techniques to improve OPMD detection and biopsy. 59 The Indian Council of Medical Research provides early detection training for dentist; more platforms are needed for standardized training.…”
Section: Challenges In the Health Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have developed systems using simple photographs, 27–29 smartphone use, 23–25,30,31 and web application 32,34 . For instance, Warin and collaborators reported a pipeline composed of segmentation and classification CNNs capable to detect and classify OPMDs in oral photographs.…”
Section: Clinical Evidence On Ai and Opmdsmentioning
confidence: 99%
“…Moreover, the research group also evidenced that phone‐integrated CNN and Cloud‐based CNN had a higher accuracy (sensitivity: 87%) when telediagnosis was employed as standard. Finally, they concluded it is useful to triage and direct oral cancer screening 34 …”
Section: Clinical Evidence On Ai and Opmdsmentioning
confidence: 99%